2020
DOI: 10.3390/biomedicines8090310
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Glioblastoma Response to Hypoxia

Abstract: Glioblastoma (GB) is the most common and deadly type of primary malignant brain tumor with an average patient survival of only 15–17 months. GBs typically have hypoxic regions associated with aggressiveness and chemoresistance. Using patient derived GB cells, we characterized how GB responds to hypoxia. We noted a hypoxia-dependent glycolytic switch characterized by the up-regulation of HK2, PFKFB3, PFKFB4, LDHA, PDK1, SLC2A1/GLUT-1, CA9/CAIX, and SLC16A3/MCT-4. Moreover, many proangiogenic genes and proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 70 publications
(105 reference statements)
0
27
0
Order By: Relevance
“…HIFs induce the transcription of hundreds of genes involved in the regulation of main cellular processes including angiogenesis, glycolysis, autophagy, motility and invasion, chemo- and radioresistance [ 58 , 59 ].…”
Section: Hypoxia In Gbmentioning
confidence: 99%
See 2 more Smart Citations
“…HIFs induce the transcription of hundreds of genes involved in the regulation of main cellular processes including angiogenesis, glycolysis, autophagy, motility and invasion, chemo- and radioresistance [ 58 , 59 ].…”
Section: Hypoxia In Gbmentioning
confidence: 99%
“…Several studies using GB cell lines and/or clinical samples support a hypoxia triggered metabolic switch towards glycolysis including the up-regulation of HK2, PFKFB3, PFKFB4, PFKFP, LDHA, PDK1, SLC2A1/GLUT-1, CA9/CA IX, PGAM1, ENO1, ENO2, ALDOA and SLC16A3/ MCT-4 genes and proteins ( Figure 4 ) [ 9 , 59 , 60 ]. Hypoxic up-regulation of many pro-angiogenic genes and proteins is also commonly observed in GB.…”
Section: Hypoxia In Gbmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study explained the role of the hypoxic state in patient-derived glioma cells to escalate the antigenic and invasive potential. The aggressive nature was accompanied by upregulated autophagy-related genes, including BCL-2 interacting protein 3 (BNIP-3) and DNA damage inducible transcript 4 (DDIT4), which are associated with chemoresistance [ 133 ]. EGFR, VEGF and RET tyrosine kinase are shown to be a contributing factor in the underlying drug-resistance mechanisms in glioblastoma patients.…”
Section: Autophagy Mediates Therapeutic Resistance In Glioblastomamentioning
confidence: 99%
“…It has also been observed that these necrotic foci have surrounding cells arranged in a pseudopalised structure and microvascular hyperplasia (capillaries) associated with rapid tumor progression and invasion, further deteriorating the prognosis of patients (Monteiro et al, 2017). One of the main characteristics observed in GBM is the presence of hypoxic nuclei regions with partial pressures of oxygen (O 2 ) below 10 mmHg, a fact that is associated with both tumor aggressiveness and resistance to chemotherapy drugs (Chédeville et al, 2020). These hypoxic areas are associated with the layer of cancer cell spreading (invasion) into the healthy brain tissue in order to evade this adverse microenvironment.…”
Section: Significancementioning
confidence: 99%